(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current research aims to study the effect of the aquarium strategy on acquiring positive thinking skills and learner’s attitudes towards this strategy in the subject of social studies among a sample of (60) male and female learners distributed into two experimental and control groups. The researcher applied to the experimental group an educational program based on the aquarium strategy, while the control group applied the usual method, it prepared a positive thinking test and a trend identification to identify the learners attitudes towards strategy, then collected and analyzed the data and concluded that there were statistically significant differences at the level of significance of (0.05) between the average scores of the learners of the two experimental and control groups in the positive thinking test , and the effectiveness of the fish tank strategy in the learning of the sixth graders in the subject of Social studies. The research ended with a set of proposals, the which is the interest in teaching learners the aquarium strategy in learning social studies.